Transitivity System on Prabowo's Representation in British Online Article: A Critical Discourse Analysis Approach - Octavia Chandra Dewi; Heriyanto Heriyanto; Elvi Citraresmana (Metahumaniora, 2021)
Articles in online media might represent media’s perspective about the object of their news. After a long process of the Indonesian presidential election in 2019, Prabowo’s appointment as the Minister of Defense in the Indonesia Presidential cabinet became hot issue. The appointment was questioned particularly due to the former general’s past actions. This study aims to analyze how the media present their news articles regarding the appointment of Prabowo as Defense Minister using the transitivity system in the Clause as Representation, and to describe how the representation of Prabowo on his appointment influenced the interpretation of the readers. The study adopted the descriptive qualitative method to analyze the data based on Critical Discourse Analysis by Fairclough (1995a) and transitivity system by Halliday (2004). The data sources were taken from the article in the British online media, TheGuardian.com. This study results in the number of positive representations that are more than the negative representations, but with a slight difference so that it can be said to be balanced.